(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Non-suicidal self-injury (NSSI) are intentional actions to provoke damage to the body tissue without suicidal intent and for purposes not socially or culturally sanctioned. Early maladaptive Schemas (EMS) are central and broad beliefs that cause negative affections and dysfunctional behaviors. The main goal of this study was to investigate through a systematic review of national and international articles if there is a relationship between non-suicidal self-injury and EMS. We used the databases: SciELO, PePSIC, Index Psi, PubMed, Scorpus, Web of Science, Lilacs, Science Direct, and PsycINFO (APA), with the terms “early maladaptive schemas”, “schema therapy”, “schemas”, and “esquemas iniciais desadaptativos”, “Non-suicidal self-injury”, “NSSI”, “self-harm”, “self-injury”, and “autolesão”. We selected five for the final analyses. Despite research suggesting that there is a relationship between EMS and NSSI, results are inconclusive, and we suggest that more empirical investigation with different samples is needed.